2001
DOI: 10.1002/1097-0142(20010801)92:3<542::aid-cncr1353>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of motility-related protein 1 (MRP1/CD9) and integrin ?3 expression in endometrial cancers

Abstract: BACKGROUND MRP1/CD9 and integrin α3 have played crucial roles in cell adhesion, motility, and signaling events. The loss of MRP1/CD9 and integrin α3 has been involved in tumor growth and metastasis of cancer cells. The aim of the current study was to clarify the clinical significance of MRP1/CD9 and integrin α3 in endometrial cancer. METHODS The expression of MRP1/CD9 and integrin α3 from the same tissue sample were examined immunohistochemically in 15 patients with normal endometrium and in 56 patients with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Several studies showed an increased expression of ␣3 integrin associated with higher metastatic ability (13,14). Using immunohistochemistry, Miyamoto (15) showed that reduced ␣3-integrin expression in endometrial cancers correlates with histological grade and metastasis. Adachi et al (16) obtained similar results in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an increased expression of ␣3 integrin associated with higher metastatic ability (13,14). Using immunohistochemistry, Miyamoto (15) showed that reduced ␣3-integrin expression in endometrial cancers correlates with histological grade and metastasis. Adachi et al (16) obtained similar results in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Among the molecules involved in cell motility, tetraspanins MRP-1/CD9 and KAI1/CD82 have been identified as suppressors of tumor spread (6,7). The expression of these tetraspanins is observed in almost all normal tissues, and these molecules are believed to mediate migration signals through forming membrane complexes with integrin receptors (8,9). Supporting these observations, numerous previous studies have shown a reduced expression of either MRP-1/CD9 or KAI1/CD82 in various tumors to correlate with the presence of distant metastasis and a poorer prognosis (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a tetraspanin family member, CD82/KAI1, believed to be a metastasis suppressor, has been shown to interact with a protein (DARC [Duffy antigen receptor for chemokines]) on endothelial cells and to induce senescence of tumor cells, 44 indicating a role in preventing ectopic dissemination. Another tetraspanin member, CD9, is believed to suppress migration signals by forming membrane complexes with integrin receptors, 4,5,45 and has been identified as a metastasis suppressor. 13,[36][37][38] However, it has not been clearly or concretely elucidated how the motility change acts, or which metastatic step is affected.…”
Section: Discussionmentioning
confidence: 99%
“…3 Numerous previous studies have shown reduced CD9 expression in various cancers, which correlated with the presence of distant metastasis and a poorer prognosis. [4][5][6][7][8][9][10][11] The clinical importance of CD9 in the diagnosis, staging, and prognosis of tumors has been growing. 12 Recently, it was reported that adenoviral transduction of CD9 inhibited lymph node metastasis in an orthotopic lung cancer model.…”
Section: Introductionmentioning
confidence: 99%